Prognostic impact of cytogenetic aberrations in AL amyloidosis patients after high-dose melphalan: a long-term follow-up study - Bochtler, Tilmann; Hegenbart, Ute; Kimmich, Christoph; Seckinger, Anja; Hose, Dirk; Goldschmidt, Hartmut; Granzow, Martin; Dreger, Peter; Ho, Anthony Dick; Jauch, Anna; Schönland, Stefan (Blood, 2016)
Cytogenetic aberrations detected by interphase fluorescence in situ hybridization (iFISH) of plasma cells are routinely evaluated as prognostic markers in multiple myeloma. This long-term follow-up study aimed to assess the prognosis of systemic light chain amyloidosis (AL) patients treated with high-dose melphalan (HDM) chemotherapy and autologous stem cell transplantation, depending on iFISH results. Therefore, we analyzed a consecutive cohort of 123 AL patients recruited from 2003 to 2014. HDM was safe, with only 1 of 123 patients dying as a result of treatment-related mortality, and effective, with a complete remission (CR) rate of 34%. Translocation t(11;14) as the most prevalent aberration (59%) led to an improved CR rate after high-dose therapy (41.2% vs 20.0%; P = .02), translating into a prolonged hematologic event-free survival (hemEFS; median, 46.1 vs 28.1 months; P = .05) and a trend for better overall survival (median, not reached vs 93.7 months; P = .07). In multivariate analysis, t(11;14) was confirmed as a favorable prognostic factor regarding hemEFS along with lower values for the difference between involved and uninvolved free light chains. Conversely, deletion 13q14, gain of 1q21, and hyperdiploidy had no significant prognostic impact. The high-risk cytogenetic aberrations t(4;14), t(14;16), and del(17p13) conferred an unfavorable prognosis, although statistical significance was reached only for univariate CR analysis in this small group of 9 patients. Thus, t(11;14) positivity in HDM-treated AL patients conferred superior CR rates and hemEFS. In view of the reduced response of t(11;14) to bortezomib, this highlights the impact of therapy on the prognostic role of cytogenetic aberrations.
Gesehen am 04.01.2019